Implementasi Metode MOORA Dengan Pembobotan Rank Order Centroid (ROC) dalam Seleksi Penerimaan Staff Gudang PT. Royal Abadi Sejahtera - Zahri Hubby Ramadhani; Nelly Astuti Hasibuan; Dito Putro Utomo (Forum Kerjasama Pendidikan Tinggi, 2022)
Warehouse staff is a job related to the storage of goods for production or production. Therefore, the person who occupies the position is required to have certain criteria. However, during this time, the warehouse head of PT. Royal Abadi Sejahtera has experienced difficulties in the process of accepting warehouse staff, because there are many applicants who come to apply and do not meet the expected criteria. The problem faced in this research is that the company is still doing the selection by looking at prospective staff willing to work, the work does not only require a level of willingness to work, but has skills, education, work experience, attitude in work and good communication. Decision Support System is a system that is used to assist in the decision-making process in an organization. In the process the Decision Support System uses several methods used in the decision-making process and one of them is the MOORA (Multi Objective Optimization on the Basis of Ratio Analysis) method and the ROC (Rank Order Centroid) method for the weighting process. The benefits that the author wants to achieve in this study are to assist the company in facilitating the process of accepting warehouse staff as input for companies in making decisions using a decision support system to provide a more objective assessment resulting from the Decision Support System.